Substitusi Tepung Kedelai dengan Tepung Biji Koro Pedang (Canavalia ensiformis) Terhadap Pertumbuhan, Survival Rate dan Efisiensi Pakan Ikan Nila Merah [Substitution Of Soybean Meal With Sword Bean Seed Meal (Canavalia ensiformis) On Growth, Survival Rate And Feed Efficiency Of Red Tilapia] - Cahyoko Yudi; Agustono Agustono; Ega Centyana (Faculty of Fisheries and Marine Universitas Airlangga, 2014)
Abstract Red tilapia is kind of freshwater culture fish is quite popular because it has several advantages compared with other types of freshwater fish. To fullfil the demand of red tilapia can be overcome by cultivation. Effort to increase the production of red tilapia is to improve the quality of feed. The purpose of this study was to try the effect of the use of sword bean seed meal on the growth rate, survival rate and feed efficiency of red tilapia. The research method is experimental with completely randomized design (CRD) with five treatments and four replications. The treatments used were: (A) sword beans seed meal at 0% and soybean meal by 50%, (B) 10% sword beans seed meal and 40% soybean meal, (C) 20% sword beans seed meal and 30% soybean meal, (D) 30% sword beans seed meal and 20% soybean meal and (E) 40% sword beans seed meal and 10% soybean meal. The main parameters that measured were growth, survival rate and feed efficiency. Secondary parameters measured were water quality. Analysis of the data using analysis of variance (ANOVA) and to know the difference between treatments using Duncan's Multiple Range Test. Results showed the administration of sword bean seed meal on feed rations provide a significantly different effect (p<0.05) on the growth and feed efficiency but not significantly on survival rate of red tilapia (p>0.05 ). Highest daily growth rate obtained on treatment B on feed containing 10% of sword bean meal (1.20 %) was significantly different than treatment A (1.02 %), C (0.88 %) , D (0.85 %) and E (0.75 %) . Lowest daily growth rate was treatment E that significantly different with treatment A and B but not significantly different with treatments C and D. Highest feed efficiency obtained on treatment B (30.29 %) was not significantly different than treatment A (27.56 %), C (25.95 %) and D (27.78 %). Lowest feed efficiency was treatment E (17.84 %) significantly different than treatment B. Subtitution of sword bean seed meal in feed rations gave result that was not significantly different effect on the level of survival of red tilapia. Water quality of red tilapia rearing media was temperature range between 25-28° C, pH 7-8, dissolved oxygen 2-5 mg/L and ammonia 1.5 to 3.0 mg/L.